Mathematical modelling in animal nutrition [ - France, James; Kebreab, E. (CABI, 2008)
Mathematical modelling is increasingly applicable to the practical sciences. Here, mathematical approaches are applied to the study of mechanisms of digestion and metabolism in primary animal species. It also explores common themes between species, and ovides an integrated approach to mathematical modelling in animal nutrition.